Peran Pemerintah Daerah dalam Pengelolaan Becak Wisata Kota Probolinggo - Pandu Satriya Hutama; Abul Haris Suryo Negoro (Journal of Tourism and Creativity, 2019)
Abstract: Tourist pedi cap as traditional transportation mode has its own characteristic and capability to create tourist’s enthuism. The driver and its pedi cap have attractive for tourists and main transportation for cruise tourists which have visited Probolinggo City since 2011. Its necessary to improve the quality service by tourist pedi cap in gainning cruise tourist’s satisfaction. The government’s roles whose derrives from local department should be optimize by designing proper programm in multi purpose and continue, through high level of quality service by tourist pedi cap. The managing of tourist pedi cap by local government should support promotion activity and development of tourism activity in Probolinggo City, and also it could rejuvenat the economic activity held by the member of pedi cap driver’s association. Keywords: Government, Managing, Tourist Pedi cap, Cruise Ship Tourism